Recommendations for Screening and Detection of Connective Tissue Disease–Associated Pulmonary Arterial Hypertension. Issue 12 (27th November 2013) - Khanna, Dinesh; Gladue, Heather; Channick, Richard; Chung, Lorinda; Distler, Oliver; Furst, Daniel E.; Hachulla, Eric; Humbert, Marc; Langleben, David; Mathai, Stephen C.; Saggar, Rajeev; Visovatti, Scott; et al.
Abstract : Objective: Pulmonary arterial hypertension (PAH) affects up to 15% of patients with connective tissue diseases (CTDs). Previous recommendations developed as part of larger efforts in PAH did not include detailed recommendations for patients with CTD‐associated PAH. Therefore, we sought to develop recommendations for screening and early detection of CTD‐associated PAH. Methods: We performed a systematic review of the literature on the screening and diagnosis of PAH in CTD. Using the RAND/University of California, Los Angeles consensus methodology, we developed case scenarios followed by 2 stages of voting. First, international experts from a variety of specialties voted anonymously on the appropriateness of each case scenario. The experts then met face‐to‐face to discuss and resolve discrepant votes to arrive at consensus recommendations. Results: The key recommendation stated that all patients with systemic sclerosis (SSc) should be screened for PAH. In addition, patients with mixed connective tissue disease or other CTDs with scleroderma features (scleroderma spectrum disorders) should be screened for PAH. It was recommended that screening pulmonary function tests (PFTs) with single‐breath diffusing capacity for carbon monoxide, transthoracic echocardiogram, and measurement of N‐terminal pro–brain natriuretic peptide (NT‐proBNP) be performed in all patients with SSc and scleroderma spectrum disorders. In patients with SSc and scleroderma spectrum disorders, transthoracic echocardiogram and PFTs should be performed annually. The full screening panel (transthoracic echocardiogram, PFTs, and measurement of NT‐proBNP) should be performed as soon as any new signs or symptoms are present. Conclusion: We provide consensus‐based, evidence‐driven recommendations for screening and early detection of CTD‐associated PAH. It is our hope that these recommendations will lead to earlier detection of CTD‐associated PAH and ultimately improve patient outcomes.